1991
DOI: 10.1007/bf00587808
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous intracerebral hematomas from vascular causes

Abstract: The aim of the present study was to assess the diagnostic accuracy of CT in determining the underlying causes of brain hematomas with a state-of-the art CT. For this purpose, CT and angiographic data of 149 subjects with spontaneous intracerebral hematomas (ICH) were statistically compared in a blind, retrospective study, taking angiography, supported when possible by surgical findings, as providing the correct diagnoses. 5 groups were distinguished on the basis of CT data: 103 patients with isolated deep ICH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
1

Year Published

1995
1995
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(7 citation statements)
references
References 18 publications
1
5
1
Order By: Relevance
“…In 15 patients with GCS 13-15, 13 (86.7%) had a favorable outcome while two (13.3%) had a poor outcome. This finding is in accordance to Schulmeyer et al [20] The value of CT scan measurements in prognostication with ICH is well known [19]. Volume of hematoma is one of the most important parameter to evaluate the severity of the condition.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In 15 patients with GCS 13-15, 13 (86.7%) had a favorable outcome while two (13.3%) had a poor outcome. This finding is in accordance to Schulmeyer et al [20] The value of CT scan measurements in prognostication with ICH is well known [19]. Volume of hematoma is one of the most important parameter to evaluate the severity of the condition.…”
Section: Discussionsupporting
confidence: 90%
“…Lampl et al [19] found a direct correlation between the size of the hematoma, depressed level of consciousness, and outcome. Patients with relatively normal consciousness (GCS Scores 13-15) rarely require surgery, whereas deeply comatose patients (GCS Scores 3-5) rarely benefit from surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Haemorrhages that involve the putamen, globus pallidum, thalamus, internal capsule, periventricular white matter, pons and cerebellum, particularly in a patient with known hypertension, are often attributed to hypertensive small-vessel disease [77]. In these patients further imaging studies investigating the underlying vascular pathology are not necessary.…”
Section: Imaging Ichmentioning
confidence: 99%
“…The value of CT scan measurements in prognostication of ICH is well known [18]. Volpin et al [19] observed that patients with a hematoma volume above 85 ml have poor outcomes.…”
Section: Discussionmentioning
confidence: 99%